Design and Development of a Speech therapy Module Using Signal Processing Techniques. (June 2017) - Mahalakshmi, P.; Dhawan, Ritwik; Ashish, Ujjwal; Sharmila, A.
Abstract: The people who have speech and language problems and have undergone surgery, trauma, etc. need the help of the speech language pathologists to improve their speech process. The pathologists many a times find it difficult to analyze the progress of the patients. So, in order to objectively evaluate the patient a system has been developed which can help the speech pathologists in analysis of the patient. A special hardware is developed for glottal vibration acquisition which is an MFCC based speech recognizer. This speech therapy module can take inputs either from the glottal vibrations or speech. All the signal processing has been done in MATLAB environment. Further, this module can extend and be used to train children to improve their vocabulary, to learn alphabets, numbers, etc.